Impact of a compression garment, on top of the usual care, in patients with breast cancer with early disturbance of the lymphatic transport: protocol of a randomised controlled trial. Issue 12 (4th December 2020) - Thomis, Sarah; Devoogdt, Nele; Bechter-Hugl, Beate; Nevelsteen, Ines; Neven, Patrick; Fourneau, Inge
Abstract : Introduction: Breast cancer-related lymphoedema (BCRL) is a common phenomenon. When lymphoedema is diagnosed late, options for treatment are diminished. Therefore, early diagnosis and treatment are very important to alter the potential deleterious evolution. Lymphofluoroscopy visualises the superficial lymphatic architecture in detail, giving the opportunity to detect a disturbance in the lymphatic transport (ie, dermal backflow) before the lymphoedema is clinically visible. The main objective is to investigate if there is an additional effect of a compression garment on top of the usual care (ie, information and exercises) in patients with early disturbance of the lymphatic transport after breast cancer treatment. Development of clinical lymphoedema and/or deterioration of the dermal backflow visualised by lymphofluoroscopy is investigated. Methodology: All patients scheduled for breast cancer surgery with unilateral axillary lymph node dissection or sentinel node biopsy in the Multidisciplinary Breast Clinic of the University Hospitals Leuven are being considered. Patients are assessed before surgery and at 1, 3, 6, 9, 12, 18, 24 and 36 months postoperatively. At each visit, a clinical assessment is performed determining the volume difference between both arms and hands (through circumference measurements and water displacement), the water content, the extracellular fluid, the pitting status and the skinfold thickness. Quality of life questionnaires are filled in. At each visit, a lymphofluoroscopy is performed as well. When a disturbance of the lymphatic transport is seen on lymphofluoroscopy, without the presence of clinical lymphoedema, the patient is randomised in either a control group receiving usual care or a preventive treatment group receiving usual care and a compression garment (whether or not combined with a glove). Ethics and dissemination: The trial is conducted in compliance with the principles of the Declaration of Helsinki (2008), the principles of Good Clinical Practice and in accordance with all applicable regulatory requirements. This protocol has been approved by the Ethical Committee of the University Hospitals Leuven. Results will be disseminated by peer-reviewed scientific journals and presentation at international congresses. Trial registration number: NCT03210311 Conclusion: The investigators hypothesise that development of clinical BCRL can be prevented and/or the dermal backflow can be stabilised or improved, if a preventive treatment with compression garment is started in the early phase of disturbance.